The handbook of race, ethnicity, crime and justice - c; Hollis, Meghan; Stowell, Jacob I., 1973- (Hoboken, NJ : Wiley Blackwell, 2018)
This Handbook presents current and future studies on the changing dynamics of the role of immigrants and the impact of immigration, across the United States and industrialized and developing nations. It covers the changing dynamics of race, ethnicity, and immigration, and discusses how it all contributes to variations in crime, policing, and the overall justice system. Through acknowledging that some groups, especially people of color, are disproportionately influenced more than others in the case of criminal justice reactions, the "War on Drugs", and hate crimes; this Handbook introduces the importance of studying race and crime so as to better understand it. It does so by recommending that researchers concentrate on ethnic diversity in a national and international context in order to broaden their demographic and expand their understanding of how to attain global change.' Featuring contributions from top experts in the field, The Handbook of Race and Crime is presented in five sections. An Overview of Race, Ethnicity, Crime, and Justice; Theoretical Perspectives on Race and Crime; Race, Gender, and the Justice System; Gender and Crime; and Race, Gender and Comparative Criminology. Each section of the book addresses a key area of research, summarizes findings or shortcomings whenever possible, and provides new results relevant to race/crime and justice. Every contribution is written by a top expert in the field and based on the latest research. With a sharp focus on contemporary race, ethnicity, crime, and justice studies, The Handbook of Race and Crime is the ideal reference for advanced undergraduate students, graduate students, and scholars interested in the disciplines such as Criminology, Race and Ethnicity, Race and the Justice System, and the Sociology of Race.'
Description based on online resource, title from digital title page (Ebook Central, viewed on May 13, 2020).
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Crime and race -- United States; Discrimination in criminal justice administration -- United States; Discrimination in law enforcement -- United States; United States -- Emigration and immigration -- Government policy; United States -- Race relations; z; z; Discrimination dans l'application des lois; x; x -- Politique gouvernementale; SOCIAL SCIENCE -- Criminology; Crime and race; Discrimination in criminal justice administration; Discrimination in law enforcement; Emigration and immigration -- Government policy; Race relations; United States